Securing DNA information from selective attacks on humans / Noor Elaiza A. Khalid, Siti Zaleha Zainal Abidin and Izyan I. Kamsani - A. Khalid, Noor Elaiza; Zainal Abidin, Siti Zaleha; I. Kamsani, Izyan (CMIWS and UiTM Press, 2011)
understanding of deoxyribonucleic acid (DNA) has grown immensely towards wealth of information about human population diversity. This diversity trait can be grouped into ethnic, family and gender. Some of these DNA traits are susceptible to certain diseases, drugs or chemicals. Thus, it is critical to secure the DNA information especially the relationship between the DNA traits and its susceptibility. This paper discusses the importance of securing this susceptibility knowledge in order to provide awareness for people, agencies or organization that involve in managing genomic information. This awareness can alert the public on the possibilities of this kind of attack. Several guidelines are also proposed to safeguard DNA information from undesirable malicious attack.